Strategies for addressing stunting from normative aspects to the four T's campaign in Bone Regency - Uyuni, Illya Tul; Fahri, Marjana (IAIN Bone, 2023)
Stunting is a health problem requiring special attention from the Bone Regency Government. Using empirical legal research, this study shows that the Bone Regency Government has adopted several strategies to reduce stunting rates, including issuing and enacting Regent Regulation No. 3 of 2020 as a solid basis for legitimacy and a normative framework for regional stakeholders to address stunting. In addition to the normative framework, massive efforts are being made on the ground, such as (i) the 4 T campaign program, (ii) distribution of bloodboosting tablets, (iii) improvement and attention to maternal health conditions during the 1000 days before birth; (iv) support in the form of supplementary feeding for pregnant women; (v) education related to stunting; (vi) child growth monitoring programs. These programs have impacted the yearon-year decline in stunting rates in Bone Regency